Navigating to Knowledge - Tuttle, M. S.; Cole, W. G.; Sherertz, D. D.; Nelson, S. J. (Methods of Information in Medicine, 1995)
One way to fulfill point-of-care knowledge needs is to present caregivers with a visual representation of the available “answers”. Using such a representation, caregivers can recognize what they want, rather than have to recall what they need, and then navigate to an appropriate answer. Given selected pieces of information from a computer-based patient record, an interface can anticipate certain knowledge needs by initializing caregiver navigation in a semantic neighborhood of answers likely to be relevant to the patient at hand. These notions draw heavily on two collaborative projects – the U.S. National Library of Medicine Unified Medical Language System® and the U.S. National Cancer Institute Knowledge Server. Both of these projects support navigation because they make the structure of medical knowledge explicit in a way that can be exploited by human interfaces.
Keywords: Navigation; Knowledge; Semantic Visualization; Point of Care; Computer-based Patient Record